Analisis Kesalahan Mahasiswa Pendidikan Matematika Dalam Menyelesaikan Soal SUBGRUP Berdasarkan Teori Newman - Samosir, Martha Indah; Sitorus, Grace Elicia; Sibarani, Khoirunnisa; Manurung, Sri Lestari (Mandalika Mathematics and Educations Journal, 2025)
This research aims to examine the types of errors students make when solving problems using Newman's procedure. A qualitative descriptive approach was employed, involving 14 students selected through purposive sampling. Data were collected through observations, written tests, and documentation, then analyzed using Newman's error analysis framework. The data analysis techniques include data reduction, data presentation, and conclusion drawing. The findings indicate that reading errors were the least common (14.28%), while process skills errors occurred most frequently (42.85%). Other types of errors included comprehension errors (21.42%), transformation errors (28.57%), and encoding errors (35.71%). These results suggest that many students struggle with processing information and systematically applying problem-solving skills. Therefore, instructional strategies should focus on strengthening conceptual understanding and providing more practice in translating problems into mathematical representations.